2021
DOI: 10.1002/ana.26046
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Nigral Neuron Density in Lewy Body Spectrum Diseases

Abstract: Parkinson's disease and other Lewy body spectrum diseases (LBDs) are associated with a specific risk for clinical depression. In the present clinicopathological study with 73 patients with LBD, we observed that the substantia nigra pars compacta dopamine neuron density was markedly lower in patients who had comorbid depression antemortem than in nondepressed patients (1.52 vs 2.32 n/mm2, p = 0.004). There were no differences in cognition, motor disease severity, antiparkinsonian medications, or disease duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…For example, in prodromal PD, depressive symptoms may gradually develop as Lewy pathology develops in the lower brainstem such as locus coeruleus and lower raphe nuclei, followed by the substantia nigra, accompanied by neuronal losses [20]. In support, postmortem studies found markedly lower neuron density in these brain regions of PD patients with depression versus without [28][29][30]. Further, neurotransmitter imbalances and alterations in the noradrenergic, serotonergic, and dopaminergic systems have also been found in association with depressive symptoms in PD [31][32][33][34].…”
Section: Plos Onementioning
confidence: 96%
“…For example, in prodromal PD, depressive symptoms may gradually develop as Lewy pathology develops in the lower brainstem such as locus coeruleus and lower raphe nuclei, followed by the substantia nigra, accompanied by neuronal losses [20]. In support, postmortem studies found markedly lower neuron density in these brain regions of PD patients with depression versus without [28][29][30]. Further, neurotransmitter imbalances and alterations in the noradrenergic, serotonergic, and dopaminergic systems have also been found in association with depressive symptoms in PD [31][32][33][34].…”
Section: Plos Onementioning
confidence: 96%
“…For instance, a recent study (Chen et al, 2021) demonstrated that the SN displayed an early pathology also in patients with MCI and Lewy body pathology vs. controls in 3 T MRI analyzed via quantitative susceptibility mapping. Another working group (Saari et al, 2021) showed that those patients with more depressive symptoms and LBD had more sparsely distributed neurons than those with no depressive symptoms. Thus, further research is needed into how certain clinical features are associated with which type of Lewy body pathology and its spread.…”
Section: Putative Pathomechanisms Of Brainstem-related Prodromal Dlb ...mentioning
confidence: 99%
“…Thirty-six postmortem cases of patients with LBDs and 19 healthy controls were included in this study. The included patients were collected from 168 postmortem cases with neuropathologically confirmed Lewy body pathology (database previously described in [6]). The inclusion criteria were available height and weight information and autopsy data, and acceptable quality of nigral tissue samples for neuronal counting.…”
Section: Subjects and Clinical Datamentioning
confidence: 99%
“…Database selection criteria and neuropathological methods have been described in detail previously [6]. Briefly, formalin-fixed and paraffin-embedded midbrain at the level of origin of the third cranial nerve was sectioned at 8 µm thick sections and stained with Luxol Fast Blue to evaluate borders of substantia nigra pars compacta (magnification 1.0) and with tyrosine hydroxylase (TH) immunohistochemistry for calculation of dopaminergic neurons.…”
Section: Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation